Perbedaan Tingkat Kelelahan Kerja Perawat Antara Shift Pagi, Sore Dan Malam Di Rsui Yakssi Gemolong - Patmoko, Bagus; , dr. Hardjanto, M.S., Sp.OK; , Dwi Astuti, SKM., M.Kes (2015)
Nurses optimal use of resources in order to improve health services required by nursing since a few years ago. This has some consequences on the extension of working hours of nurses and one is to employ nurses exceeded the predetermined time or impose a work shift. The purpose of this study was to determine differences in fatigue to shift nurse in the morning, afternoon and evening at RSUI YAKSSI Gemolong. The method uses observational analytic research with cross sectional approach. Samples taken calculated by the method Solvin obtained by 47 nurses were divided in shifts morning, afternoon, and evening. Measuring instruments used to measure the fatigue is of KAUPK2. Data analysis tool used by Kruskal Wallis analysis tools SPSS. The results showed no significant differences in fatigue between morning shift to afternoon shift (p-value = 0.000 <0.05), no significant differences in fatigue between morning shift with night shift (p-value = 0.001), and there was no difference in fatigue which means the afternoon shift to the night shift (p-value = 0.285). The level of fatigue in the morning work shift lightweight majority (88.2%), fatigue afternoon shift had mild (56.3%), and the night shift have mild fatigue (78.6%).